A return look at dormant season irrigation strategies - Schlegel, Alan J., author; Stone, Loyd R., author; Dumler, Troy J., author; Lamm, Freddie R., author (Colorado State University. Libraries, 2012)
Many of the irrigation systems today in the Central Great Plains no longer have the capacity to apply peak irrigation needs during the summer and must rely on soil water reserves to buffer the crop from water stress. Considerable research was conducted on preseason irrigation in the US Great Plains region during the 1980s and 1990s. In general, the conclusions were that in-season irrigation was more beneficial than preseason irrigation and that often preseason irrigation was not warranted. The objective of this study was to determine whether preseason irrigation would be profitable with today's lower capacity wells. A field study was conducted at the KSU-SWREC near Tribune, Kansas, from 2006 to 2009. The study was a factorial design of preplant irrigation (0 and 3 in), well capacities (0.1, 0.15, and 0.20 in day-1 capacity), and seeding rate (22,500, 27,500, and 32,500 seeds a-1). Preseason irrigation increased grain yields an average of 16 bu a-1. Grain yields were 29% greater when well capacity was increased from 0.10 to 0.20 in day-1. Crop water productivity (CWP, grain yield divided by crop water use) was not significantly affected by well capacity or preseason irrigation. Preseason irrigation was profitable at all well capacities. At well capacities of 0.10 and 0.15 in day-1, a seeding rate of 27,500 seeds a-1 was generally more profitable than lower or higher seeding rates. A higher seeding rate (32,500 seeds a-1) increased profitability when well capacity was increased to 0.2 in day-1.
Proceedings of the 24th annual Central Plains irrigation conference
Presented at Proceedings of the 24th annual Central Plains irrigation conference held on February 21-22 in Colby, Kansas.